Contemporary Sikhism in the context of Malaysia with special reference to the Sikh community in Selangor - Asma binti Muhammad Uthman El-Muhammady (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
This study explores the Sikh's understanding and practice of Sikhism in the context of Malay-Muslim majority society, Malaysia. It is assumed that the multi-religious and multi-racial nature of Malaysian society somehow would affect the Sikhs' understanding and practice of their religion. The difficulties in practicing and getting SikkhÊ education are among the issues in the practice and understanding of Sikhism in the Malaysian context. Apart from the understanding and practice, it is of equal importance of the Sikhs' perception on Muslims and Islam in Malaysia is also investigated in this study. This study shows that the privileged status of Islam in Malaysia causes some concerns and complaints on the part of several adherents of Sikhism. This study has been able to highlight this issue objectively and emphatically. Using in-depth interview method, (30) Sikhs have been interviewed from the low, the middle and the higher income groups as well as their religious experts. The objective of this explorative study is to identify the Sikhs' condition as a religious community in a majority-minority context with Islam as the privileged religion. It is aimed at preserving and promoting good inter-religious relationship and understanding among Malaysian communities so that the non-Muslim religion can continue to be practiced in peace and harmony, as provided by the Constitution of Malaysia. It is discovered that in terms of practice, the Sikhs are following the Sikh Rehit MaryÉdÉ (The Sikh Code of Conduct) of the KhÉlsÉ Order of the Tenth GurË, Gobind Singh (d.1708) though not fully successful in observing the Sikhs' Article of Faith i.e. the Five Ks and abstaining from the ChÉr-kurehit (Four Taboos). Some members of the Sikh community also express some difficulties and obstacles they face in practicing their religion in Malaysia while to some of them, Malaysia is considered as the second home for Sikhism after the Punjab. In terms of understanding of the fundamental concepts, the Sikhs are united in their understanding of the Oneness of God as well as the position of GurËs and GurË Granth SÉhib. However, they have differences of opinion with regard to other concepts like the concept of karma (human action) and views on some of the KhÉlsÉ Code of Discipline.